Peningkatan Pendapatan Petani Penggarap Dalam Transaksi Maro Pada Tanah Pertanian - Adi Gunawan; Win Yuli Wardani; Febrina Heryanti (Institut Teknologi dan Bisnis Semarang, 2023)
Maro transactions are conventional transactions that have been practiced by farmers and agricultural land owners for a long time. This transaction was carried out for several reasons, namely because sharecroppers did not have their own land, the economic needs of both farmers and the need for food, to make productive use of land and to provide jobs to landless farmers. However, in practice it turns out that these transactions do not provide a sense of justice for farmers and are more profitable for landowners. Therefore legal counseling is carried out directly to farmers and landowners, so that they can influence and change the form of the transaction so that it can be mutually beneficial between farmers and landowners.